If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1b + 4 = 1 Reorder the terms: 4 + -1b = 1 Solving 4 + -1b = 1 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1b = 1 + -4 Combine like terms: 4 + -4 = 0 0 + -1b = 1 + -4 -1b = 1 + -4 Combine like terms: 1 + -4 = -3 -1b = -3 Divide each side by '-1'. b = 3 Simplifying b = 3
| b+17=3 | | a+7=13 | | 7(h-5)=14 | | (4x-11)-(x-12)= | | 3A*6A=14 | | 3(c+1)=-12 | | 5(d-3)=40 | | 3A*6A= | | 4x+x-2=3x | | 5x+7=x+31 | | 4w+18=54 | | 3t-5=28 | | 9s-4=32 | | 6-5p=-19 | | 7+3y=19 | | 4y=-88 | | r^2-2r+10=0 | | 18=2xn | | x^2-x-414=0 | | 9x+18x-x-2= | | 2x^4-8x^3+3x^2-12x=0 | | -2(5-2x)=8(2x+1) | | (2x-4x)+14+24x=16 | | t^2=4t | | (c^2+8c+19)=0 | | 6x+3=5-2(4+-1) | | x^2+12x+6=-5 | | 4y=2y+18 | | y=0.4x^2+5.4x+14.8 | | x^2-11001x-462000=0 | | c^2-9c+8= | | X^2-kx+36=0 |